Christian interpretation of anthropological guidelines for lawmaking - Mykola, Nesprava; Mykhailo, Rizak; Vladlen, Volkov; Voluiko, Oksana; Skrypa, Yevhenii (Cuestiones Políticas, 2020)
The objective of the article is to reveal the main foundations of human creation enshrined in Christian doctrine, which serve as axiological guidelines for the elaboration of laws, providing a humanistic content of the law. The research methodology is based on dialectical, formal-dogmatic, sociological, comparative-legal and documentary methods. The results of the study demonstrate that theocentrism and anthropocentrism are not opposed to each other in Christianity, but rather are combined into an integrated theological and anthropological picture of a man. Considering this prism of legal consciousness as a reflection of the supreme law of God, the authors refute the secular-positivist view of "homo juridicus" as a soulless subject of law and emphasize the role of the Gospel commandments as a guide. for the elaboration of laws. It is concluded that the Christian vision of the synergistic interaction of the human being and the legislator through the unity of three incarnations: "homo spiritus" - "homo sapiens" - "homo juridicus" indicates the values, which are designed to ensure humanization of the law through the humanization of social relations in general.